Tracking RNA with light: selection, structure, and design of fluorescence turn-on RNA aptamers - Trachman, Robert J. (Q Rev Biophys, 2019)
Fluorescence turn-on aptamers, in vitro evolved RNA molecules that bind conditional fluorophores and activate their fluorescence, have emerged as RNA counterparts of the fluorescent proteins. Turn-on aptamers have been selected to bind diverse fluorophores, and they achieve varying degrees of specificity and affinity. These RNA-fluorophore complexes, many of which exceed the brightness of green fluorescent protein (GFP) and their variants, can be used as tags for visualizing RNA localization and transport in live cells. Structure determination of several fluorescent RNAs revealed that they have diverse, unrelated overall architectures. As most of these RNAs activate the fluorescence of their ligands by restraining their photoexcited states into a planar conformation, their fluorophore binding sites have in common a planar arrangement of several nucleobases, most commonly a G-quartet. Nonetheless, each turn-on aptamer has developed idiosyncratic structural solutions to achieve specificity and efficient fluorescence turn-on. The combined structural diversity of fluorophores and turn-on RNA aptamers has already produced combinations that cover the visual spectrum. Further combined molecular evolution and structure-guided engineering is likely to produce fluorescent tags custom-tailored to specific applications.